Distinguishing Dalālah, 'Illat, and Manāṭ al-Ḥukm in Uṣūl al-Fiqh and Their Relevance to Contemporary Ijtihād with Special Reference to Islamic Economics - Tarig Mansour (LPPM Ma'had Aly Sunan Drajat Lamongan, 2026)
Within the discipline of uṣūl al-fiqh, three fundamental concepts—dalālah, 'illat, and manāṭ al-ḥukm—are frequently misunderstood or conflated by students and even practitioners of Islamic law. This conceptual ambiguity poses a serious methodological challenge to accurate legal reasoning. This study aims to analyze the epistemological differences between dalālah, 'illat, and manāṭ al-ḥukm, and to implement this analytical framework within contemporary ijtihād, with a particular focus on issues in Islamic economics and muamalah. This research employs a qualitative-descriptive approach using library research. Primary sources include classical and contemporary uṣūl al-fiqh literature, including works by Al-Ghazali, Al-Amidi, Al-Shatibi, Ibn Qayyim, Wahbah al-Zuhayli, and Jasser Auda. Data analysis was conducted using comparative-conceptual analysis and content analysis methods. The findings reveal that dalālah operates within the textual-semantic domain concerning linguistic meanings from sacred texts; 'illat operates within the domain of legal causality representing the rational-syar'i reason behind a ruling; and manāṭ operates within the domain of empirical reality concerning the actual application of law to concrete cases. These three concepts form a hierarchical epistemological structure: dalālah → 'illat → manāṭ. An integrated yet differentiated understanding of these three concepts is a methodological prerequisite for valid, adaptive, and responsive contemporary ijtihād, particularly in addressing modern economic and financial transactions not explicitly mentioned in classical texts.